Effect of Hydrophobic Silica-Based Admixture on the Physical Performance and Durability of Waterproof Geopolymer Composite - Maisarah Nur Noraini,; Ahmad Zailani, Warid Wazien; Mohd Apandi, Nazirah; Muhammad Sofian Abdullah,; Norlia Mohamad Ibrahim,; Sinarta, I. Nengah; Agustini, Ni Komang Ayu; Dian M. Setiawan, (International Journal of Integrated Engineering, 2025)
Sustainability construction technology initiatives have a great concern for green construction materials that offer high durability properties comparable to conventional alternatives. Geopolymer concrete, synthesised from industrial by-product-based precursors such as fly ash and slag, presents an eco-friendly alternative to Portland cement, but requires improved water resistance for widespread adoption and high durability binders. This study systematically evaluates polydimethylsiloxane (PDMS) as a hydrophobic modifier (0-5% by binder weight) to enhance the performance of geopolymers. Comprehensive testing revealed PDMS's dual mechanism: surface modification (an increase in contact angle from 40.1° to 97.3° at a 4% dosage) and pore structure refinement (a 76% reduction in water absorption at a 5% dosage). Mercury intrusion porosimetry showed PDMS effectively seals micropores while creating strategically isolated macropores that maintain low permeability. The 5% dosage emerged as optimal, delivering balanced surface hydrophobicity (93.9° contact angle) with superior matrix densification (0.93% water absorption). These findings establish PDMS-modified geopolymer as a viable, durable construction material for moisture-prone environments, addressing both sustainability and performance requirements in modern and resilient infrastructure.